Treatment and complications of PCOS in adolescents - what’s new in 2023? - Jakubowska-Kowal, Karolina; Skrzyńska, Karolina; Gawlik-Starzyk, Aneta (Frontiers in Endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is a disease affecting as many as about 10% of women of reproductive age, also 3-11% of teenage patients, and can lead to numerous complications and coexists with many diseases. Research is ongoing to establish an appropriate diagnostic and therapeutic path for adolescent girls with PCOS. It is also important to implement appropriate check-ups among teenagers with PCOS in order to prevent PCOS complications and initiate appropriate treatment as soon as possible and prevent the long-term consequences of these complications. The relationship between the cooccurrence of PCOS and diseases such as metabolic syndrome, hypertension, obesity, insulin resistance, type 2 diabetes and non-alcoholic fatty liver disease (NAFLD) is increasingly being investigated. A great attention is also being paid to the problem of mental health in this group of patients. In our study, we will review the latest reports on the treatment of PCOS and look at the complications that this syndrome can cause.